1972
DOI: 10.1136/jcp.25.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two triiodothyronine uptake techniques for the assessment of thyroid function

Abstract: (Goodhead and McAlister, 1970). Nonetheless, all these procedures have the disadvantage that they alter the equilibrium between bound and free hormone so that the percentage uptake increases with time. Furthermore, as the rate of dissociation is temperature dependent, both temperature and the duration of incubation must be rigidly standardized. Recently Amersham have introduced the Thyopac kit based on the use of a molecular sieve with a pore size such that only the free fraction can enter its matrices. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The Thyopac-3 results obtained here gave a normal range of 95 to 122% which is similar to the 97 to 122 % range found by Chan et al (1972). When the Thyopac-4 results are used with the Thyopac-3 results to give values for TFTI, discrimination between different thyroid conditions is better than using the Thyopac-3 or Thyopac-4 kits alone.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The Thyopac-3 results obtained here gave a normal range of 95 to 122% which is similar to the 97 to 122 % range found by Chan et al (1972). When the Thyopac-4 results are used with the Thyopac-3 results to give values for TFTI, discrimination between different thyroid conditions is better than using the Thyopac-3 or Thyopac-4 kits alone.…”
Section: Discussionsupporting
confidence: 85%
“…Thyopac-3 kits have the advantage that the results are not time dependent compared with those of Triosorb kits (Chan et al, 1972). Watson and Lees (1973) have discussed the limitations of PBI estimations, including iodine contamination, compared with serum T4 estimations and have concluded that the serum PBI test is obsolete as a test of thyroid function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were counted in a y-counter for 100 s (minimum of 3 x 10 4 counts). This test has recently been evaluated (Chan, McAlister and Landon, 1972).…”
Section: Thyopac-jmentioning
confidence: 99%
“…Serum T4 was measured by radioimmunoassay (reagents from North East Thames Region Immunoassay Unit), THUT was measured using a modification of the 'Thyopac Three' method (Chan et al, 1972). TSH levels were assessed by an immunoradiometric assay as described by Newman et al (1985) except that a '"I labelled mouse monoclonal anti-TSH antibody was used in place of the affinity-purified, polyclonal, labelled sheep anti-TSH antibody.…”
Section: Methodsmentioning
confidence: 99%